Kredibilitas Social Media Influencer Marketing terhadap Minat Beli: Hedonisme Sebagai Moderasi - S.A Marivan HR; Kurniawati Kurniawati; Yolanda Masnita (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose Social media influencers (SMIs) have become a major source of influence in influencing consumer behaviour in the decision-making processes. As such, this justifies scholarly attention in understanding how SMI translates its meaning into preferred brands and drives consumers positive behavioural intentions. This paper aims to examine the impact of SMIs credibility, as manifested by trustworthiness, attractiveness, and expertise, along with the moderating effects of hedonism, on followers purchase intention.Methodology Sampling data was collected by purposive sampling and obtained 174 valid samples of Instagram social media users. The data were analyzed using the SEM-PLS methodFindings The results show that SMIs trustworthiness have positive effect on followers purchase intention. Moreover, the moderating effect of hedonism on the relationship between SMIs trustworthiness, attractiveness, and expertise, does not affect followers' purchase intention. Originality/Novelty This research contributes to the SMI literature by examining the influence of SMIs source credibility, along with the moderating effect of hedonism, on followers purchase intention. Implications At the end of the day, many organizations choose to engage SMIs for advertising given their high number of followers and expertise in their niche. However, regarding merely these requirements can result in wrong decisions. The findings of this research indicate that companies need to carefully select an SMI who is perceived as trustworthy by their followers to generate purchase intent.